Narrative comprehension and engagement with e-books vs. paper-books in autism spectrum condition. (April 2020) - Wainwright, Bethany R; Allen, Melissa L; Cain, Kate
Background and aims: Children with autism spectrum condition often have specific difficulties with narrative comprehension, a skill which has a strong association with both concurrent and longitudinal reading comprehension. A better understanding of narrative comprehension skills in autism spectrum condition has the potential to provide insight into potential later reading comprehension difficulties and inform early targeted intervention. In the current study, the main objective was to investigate how differences in the medium of story presentation (paper-book vs. e-book) and differences in story narration (adult narration vs. in-app narration) would influence narrative comprehension in general, and between groups (autism spectrum condition and a receptive language-matched control group). We were also interested in how task engagement (visual attention and communication) differed between group and conditions and whether task engagement was related to narrative comprehension. Method: Forty-two children with autism spectrum condition and 42 typically developing children were read a story either via a paper-book or an e-book with interactive and multimedia features. The e-book was either narrated by the experimenter (adult narrated iPad condition) or narrated by an in-app voiceover (e-book narrated iPad condition). Children's behaviour during storybook reading was video recorded and coded for engagement (visual attention and communication). They then completed two measures of narrative comprehension: multiple-choice questions (measuring recall of literal information) and a picture ordering task (measuring global story structure). Results: Contrary to predictions, we did not find any significant group or condition differences on either measure of narrative comprehension, and both groups demonstrated a similar level of narrative comprehension across the three conditions. We found differences in engagement between conditions for both groups, with greater visual attention in the e-book conditions compared to the paper-book condition. However, visual attention only significantly correlated with narrative comprehension for the typically developing group. Conclusion: Overall, this study suggests that children with autism spectrum condition are just as able as language-matched peers to comprehend a narrative from storybooks. Presenting a story on an iPad e-book compared to a paper-book does not influence narrative comprehension, nor does adult narration of the story compared to in-app narration. However, on-task engagement is linked to narrative comprehension in typically developing children. Implications: Taken together, our findings suggest that e-books may be more successful than paper-based mediums at encouraging visual attention towards the story, but no better at supporting narrative comprehension and eliciting communication.